Exploring the role of self-control across distinct patterns of cyber-deviance in emerging adolescence - Whitten, Tyson (International journal of offender therapy and comparative criminology, 2024)
A disproportionally large number of adolescents engage in cyber-deviance. However, it is unclear if distinct patterns of adolescent cyber-deviance are evident, and if so, whether and to what extent low self-control is associated with different patterns of cyber-deviance. The current study addressed this research gap by examining the relationship between self-control and distinct latent classes of adolescent cyber-deviance net of potential confounders among a cross-sectional sample of 1793 South Australian adolescents. Four latent classes were identified, each characterized by varying probabilities of involvement in six types of cyber-deviance that were measured. The versatile class (n = 413) had the lowest average level of self-control, followed by the harmful content users (n = 439) and digital piracy (n = 356) classes, with the abstainer class (n = 585) characterized by the highest self-control. Analysis of covariance indicated that the abstainer group had significantly higher self-control than other classes of cyber-deviance. Although the versatile class had noticeably lower average self-control scores than the harmful content users and digital piracy groups, this difference was not significant after correcting for multiple comparisons. Collectively, these findings suggest that self-control appears to distinguish between those who do and do not engage in cyber-deviance but may not distinguish between distinct patterns of cyber-deviance net of other factors.